AB0954 A randomised, double-blind trial comparing the efficacy, safety and immunogenicity of msb11022, a proposed biosimilar of adalimumab, versus adalimumab originator in patients with moderate-to-severe plaque psoriasis. (12th June 2018) - Hercogová, J.; Papp, K.A.; Edwards, C.J.; Chyrok, V.; Halady, T.; Ullmann, M.; Vlachos, P.
Abstract : Background: Adalimumab is a fully human anti-TNF mAb, indicated for the treatment of multiple inflammatory disorders. MSB11022 is a proposed adalimumab biosimilar that has shown analytical similarity [1] and bioequivalence to US-licensed and EU-approved adalimumab originator, as well as comparable safety, tolerability and immunogenicity in a phase I trial [2]. Objectives: The aims of this multicentre, double-blind, parallel-group, 52-week phase III study (AURIEL-PsO, NCT02660580 ) were to demonstrate equivalence in efficacy (Psoriasis Area and Severity Index [PASI] 75) and to compare the safety and immunogenicity of MSB11022 vs. adalimumab originator in patients with moderate-to-severe chronic plaque psoriasis. This study was designed in-line with the biosimilar regulatory framework as part of the totality of evidence to confirm similarity and rationale for extrapolation. Methods: A total of 443 eligible patients (391 evaluable, including 43 with psoriatic arthritis) from 69 sites in 12 countries were randomised 1:1 and treated with MSB11022 (n=202) or adalimumab originator (n=189) (80 mg subcutaneously [SC] on day 1; 40 mg SC every other week from weeks 2−14). The primary endpoint was PASI 75 at week 16; equivalence was established if the 95% confidence interval (CI) for the treatment difference was within ±18%. Secondary endpoints included % change from baseline in PASI (equivalence confirmed if 95% CI within ±15%), Physician Global Assessment (PGA), quality of life (QoL), immunogenicity and safety. Interim results at week 16 are presented. Results: Patient baseline characteristics were comparable between MSB11022 and adalimumab originator groups: mean age 44.8 vs. 42.4 years, male 66.8% vs. 68.3%, mean PASI score 20.7 vs. 21.2, respectively. PASI 75 scores were 89.6% for MSB11022 and 91.5% for adalimumab originator (difference −1.9% [95% CI −7.82–4.16]). Mean % change from baseline in PASI was −90.6% for MSB11022 and −91.7% for adalimumab originator (difference −1.0% [95% CI −1.23–2.98]). PGA and QoL scores were comparable between treatment groups. The incidence of treatment-emergent adverse events (TEAEs)/serious TEAEs was 51.1/3.6% for MSB11022 and 53.2/2.7% for adalimumab originator. Immunogenicity profiles of MSB11022 and adalimumab originator were also similar and consistent. Conclusions: Week 16 results of this phase III confirmatory study demonstrated equivalent efficacy and similar safety and immunogenicity profiles for MSB11022 vs. adalimumab originator at 16 weeks in patients with moderate-to-severe chronic psoriasis. References: [1] Magnenat L, et al. Demonstration of physicochemical and functional similarity between the proposed biosimilar adalimumab MSB11022 and Humira®. MAbs. 2017;9:127–139. [2] Hyland E, et al. Comparison of the pharmacokinetics, safety, and immunogenicity of MSB11022, a biosimilar of adalimumab, with Humira® in healthy subjects. Br J Clin Pharmacol. 2016;82:983–93. Disclosure of Interest: J. Hercogová Grant/research support from: Fresenius Kabi, Consultant for: Fresenius Kabi, K. Papp Grant/research support from: Fresenius Kabi, C. Edwards Grant/research support from: Fresenius Kabi, Consultant for: Fresenius Kabi, V. Chyrok Employee of: Fresenius Kabi, T. Halady Employee of: Fresenius Kabi, M. Ullmann Employee of: Fresenius Kabi, P. Vlachos Consultant for: Fresenius Kabi